Roles of Goverment and non government organizations in reconciling the communities in the Ambon conflict - Zulkipli Lessy (Fak. Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2013)
st,1/nr,c.1/ws.c.2-3